Monte Carlo Computation of the Influence of Carbon Contamination Layer on the Energy Distribution of Backscattered Electrons Emerging from Al and Au - A. M. D. Assa’d (Jordan Journal of Physics, 2025)
The influence of carbon contamination layer (5nm) on the energy distribution of backscattered electrons (BSEs) emerging from the top of Al- and Au-substrates at a wide range of normal primary electron energies (EP = 0.5-20keV) has been theoretically examined. The study is based on using a CASINO Monte Carlo model. Generally, the results show a clear effect of the contamination on the backscattering coefficient and the energy distribution of backscattered electrons. This appeared as a reduction of the number of BSE emerging from the surface with energies close to the primary energy. For primary energy less than 5keV, the contamination effects are clearly seen in the reduction of the number of BSEs emerging with energy close to EP and the increment of the number of BSEs with low energies. The backscattered electron spectrum starts with a wide peak at low energies and becomes sharper as the primary energy increases. For high primary electron energies (10-20keV), the influence of the carbon contamination layer is restricted on the energy distribution of the backscattered electrons with energies above 95% of the primary energy. The influence of the carbon contamination layer was observed more clearly for the Au-substrate than for the Al-substrate as a reduction of the number of backscattered electrons. Keywords: Backscattered Electrons, Monte Carlo Model, CASINO, Backscattering Coefficient, Carbon Contamination, Energy Distribution.